A prospective observational study on prescribing patterns of drugs used in alcoholic liver disease patients at tertiary care teaching hospital - S., Zeebaish; P., Hemalatha; P. V. S. N., Eswari; T., Kodandaraman; P., Lakshmi; G., Apoorva (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Rational drug prescribing can be defined as appropriate drugs prescribed in the right dose, at correct time intervals and for a sufficient duration. Alcoholic Liver Disease (ALD) and its complications are the principle cause for morbidity and mortality rate and accounts for elevated social and economic costs. The drug use will be a challenge for the physicians as there was no specific treatment for ALD, and decisions regarding treatment are critically depends on the symptoms and complications. Methods: A uni-centric prospective (observational) study was conducted for a period of 6months, to evaluate the current prescribing patterns used in treating ALD. All the patients admitted with diagnosis of ALD in General medicine department, both male and female medical wards were included in the study. General medicine outpatient department, special population such as pregnancy and psychiatry, patients below 18years and those who are not willing to sign in informed consent form was excluded from the study. Results: Number of males (98.02%) between age group 31-40years (29.6%) was more prone when compared to females (1.77%). Portal hypertension (30.35%) followed by jaundice (11.30%) and Ascites (10.71%) were frequently observed complications associated co-morbidities with ALD. WHO prescribing indicators showed deviation from there standard reference values. Diuretics (15.73%), antibiotics (13.14%), vitamin supplements (11.11%) and antacids (10.13%) categories were the most commonly prescribed for patients. The drugs prescribed from NLEM-2015 (82.11%) shows deviation from standard values. Conclusions: Futhermore, multi-centered studies should be conducted to draw best results on prescribing patterns of ALD in India.